Study of the compression strength and water absorption of concretes produced with addition of construction and demolition rubble and sludge from water treatment stations - Sales, Almir (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper presents the study of compression strength and water absorption of concretes produced with the addition of rubble from construction and demolition sites and sludge from water treatment plants, aiming to assess the possibility of replacing natural aggregates (sand and fine crushed stone) with those residues. Such replacement will make it possible to reduce the environmental impact caused by the extraction of natural aggregates, saving them for future generations.